Dynamism and the Ageing of a Japanese 'New' Religion Transformations and the Founder - Baffelli, Erica (Bloomsbury Academic, 2018)
"This book is available as open access through the Bloomsbury Open programme and is available on www.bloomsburycollections.com. This book examines the trajectory and development of the Japanese religious movement Agonshu and its charismatic founder Kiriyama Seiyu. Based on field research spanning 30 years, it examines Agonshu from when it first captured attention in the 1980s with its spectacular rituals and use of media technologies, through its period of stagnation to its response to the death of its founder in 2016. The authors discuss the significance of charismatic leadership, the 'democratisation' of practice and the demands made by movements such as Agonshu on members, while examining how the movement became increasingly focused on revisionist nationalism and issues of Japanese identity. In examining the dilemma that religions commonly face on the deaths of charismatic founders, Erica Baffelli and Ian Reader look at Agonshu's response to Kiriyama's death, looking at how and why it has transformed a human founder into a figure of worship. By examining Agonshu in the wider context, the authors critically examine the concept of 'new religions'. They draw attention to the importance of understanding the trajectories of 'new' religions and how they can become 'old' even within their first generation.